Understanding Chinese consumption: The impact of hukou - Christian Dreger; Tongsan Wang; Yanqun Zhang (European University Viadrina, Department of Business Administration and Economics, 2013)
The Chinese growth miracle was based on exports and investment in recent years. While strong output growth has been maintained even during the financial crisis, the imbalances within the country increased. To return to a more sustainable path of development, policies are directed to improve the role of private consumption. However, the institutional framework is an impediment to the transformation, as it weakens the incentives of households to consume. Besides a low degree of social security and highly regulated financial markets, we stress the relevance of the hukou system as the main driver for modest consumption, especially in recent years. After controlling for different income levels, the average propensity to consume is significantly lower for migrants, as their access to public services is limited. The downward pressure on consumption will increase in the future. The urbanization strategy of the government will likely raise the number of migrants with limited hukou rights, if it is not accompanied by respective reforms. Therefore, the transformation towards consumption driven growth is endangered without further reforms.
Keywords: E21; O15; R23; 330; Chinese private consumption; urbanization strategy; hukou system